Clinical Perspectives on 3D Bioprinting Paradigms for Regenerative Medicine. Issue 1 (2019) - Loai, Sadi; Kingston, Benjamin R.; Wang, Zongjie; Philpott, David N.; Tao, Mingyang; Cheng, Hai-Ling Margaret
No abstract available